Biochemical evidence of free radical-induced lipid peroxidation for chronic toxicity of endosulfan and malathion in liver, kidney and gonadal tissues of wistar albino rats - (:unkn) unknown (My University, 2008)
This paper documents the findings of a research aimed at determining the levels of malondialdehyde (MDA) used for measuring the oxidative damages in liver, kidney and gonadal tissues in rats due to high doses of endosulfan and malathion. Evidence on the following results are presented: there are chronic effects of sublethal doses of endosulfan and malathion on tissue MDA levels. Oxidative stress is important in the mode of action of these insecticides. There are important and significant increases in the levels of MDA in all organs in relation to the applied dose. Also, MDA values are higher in experimental groups administered endosulfan than the groups administered malathion. These results suggest that endosulfan may cause more oxidative damages than malathion.
Keywords: Endosulfan; Lipid peroxidation; Malathion; Malondialdehyde; Rat